2023
DOI: 10.1002/sej.1493
|View full text |Cite
|
Sign up to set email alerts
|

Strategic leaders' ecosystem vision formation and digital transformation: A motivated interactional lens

Emmanuelle Reuter,
Steven Floyd

Abstract: Research SummaryThe question of why and how strategic leaders differ in the ecosystems they envision is central to firms' digital transformation. We unpack the cognitive microfoundations of how strategic leaders form their ecosystem vision—a mental model of a firm's multilateral complementarities with its partners to realize a value proposition. Our motivated interactional lens emphasizes the role of strategic leaders' cognitive motivation for shaping four interaction types with (prospective) partners: partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 158 publications
0
2
0
Order By: Relevance
“…Clearly, then, it is a core task of strategic leaders to form and execute a vision for ecosystem development strategically. In this regard, the Special Issue article by Reuter and Floyd (2024), entitled "Strategic leaders' ecosystem vision formation and digital transformation: A motivated interactional lens," makes a valuable contribution by developing novel theory about why and how strategic leaders differ in the digital ecosystems they envision. The authors conceptualize ecosystem visions as mental models of the firm's multilateral complementarities with (prospective) partners, which are developed through leaders' social interactions with the ecosystem.…”
Section: The Role and Influence Of Strategic Leadersmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, then, it is a core task of strategic leaders to form and execute a vision for ecosystem development strategically. In this regard, the Special Issue article by Reuter and Floyd (2024), entitled "Strategic leaders' ecosystem vision formation and digital transformation: A motivated interactional lens," makes a valuable contribution by developing novel theory about why and how strategic leaders differ in the digital ecosystems they envision. The authors conceptualize ecosystem visions as mental models of the firm's multilateral complementarities with (prospective) partners, which are developed through leaders' social interactions with the ecosystem.…”
Section: The Role and Influence Of Strategic Leadersmentioning
confidence: 99%
“…Externally, digital transformation has implications for the firm's ecosystem (i.e., Adner, 2021). Reuter and Floyd (2024), in this special issue, suggested that digital transformation entails an ecosystem challenge, requiring firms to complement their value proposition with partners' offerings. Thus, a key strategic choice is whether firms will choose to compete independently or deepen and/or widen their participation in external ecosystems.…”
Section: Commonalities and Variationsmentioning
confidence: 99%